The Relationship of Basic and Instrumental Activities of Daily Living With the Risk of Developing Pressure Ulcer - Sahar Mohammadi; Forough Rafii; Tahmine Salehi; Hamid Haghani (Iran University of Medical Sciences, 2018)
Background: The basic and instrumental activities of daily living are prerequisites for living with a good quality of life. On the contrary, lack of movement and physical inactivity are considered as the main cause of pressure injuries. Accordingly, this study aimed to determine the relationship between the basic and instrumental activities of daily living with the risk of pressure ulcers in patients referred to educational health care centers affiliated to Iran University of Medical Sciences in 2017.  Methods: This descriptive, cross-sectional study was conducted on 200 patients referred to internal and surgical clinics of hospitals affiliated to Iran University of Medical Sciences. The sample was recruited by cluster sampling method. The study questionnaires included four sections: a demographic from, Katz Scale of Basic Activities of Daily Living (BADL), Lawton Scale of Instrumental Activities of Daily Living (IADL), and Braden pressure ulcer risk assessment scale. Data was analyzed by Independent t test, ANOVA, Pearson correlation coefficient, and Spearman correlation test using SPSS-PC V. 24. Results: With higher dependence in performing BADL and IADL, the risk of pressure ulcer development increased (P<0.001). The relationship was even higher with regard to IADL. Dependence in all subscales of BADL and IADL was directly related to the risk of developing pressure ulcer (P<0.001). Conclusion: The degree of dependence in BADL and IADL can be considered as one of the predictors of pressure ulcer development. It is necessary to plan appropriately to increase the independency of patients in performing such activities.